(En)Gendering Vulnerability: Immigrant Service Providers’ Perceptions of Needs, Policies, and Practices Related to Gender and Women Refugee Claimants in Atlantic Canada - Tastsoglou, Evangelia; Abidi, Catherine Baillie; Brigham, Susan M.; Lange, Elizabeth A. (Refuge: Canada's Journal on Refugees, 2014)
As part of a multi-phased study exploring the experiences of refugee claimants in Atlantic Canada, this article focuses on the experiences and perceptions of immigrant service providers in relation to gender and women refugee claimants. Given the paucity of research on refugees in Atlantic Canada and on the particular perspectives of service providers, we have located this part of our research in the intersection of state policies and civil society practices, in particular service providers’ and NGO practices vis-à-vis refugees and refugee claimants. To contextualize our study we briefly trace global and national trends in migration and refugee issues, specifically increasing refugee deterrence policies that restrict claimants’ access to protection and settlement services. Findings highlight the recognition of gender-specific needs but also the lack of a gendered analysis of women refugee claimants, uneven accessibility to support services across the Atlantic region, challenges in navigating services, low cultural competence of institutional social and health service providers, and the rise of a punitive deterrence culture.